2013
DOI: 10.1530/joe-13-0391
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin gene products, receptors, and GOAT enzyme: biological and pathophysiological insight

Abstract: Ghrelin is a 28-amino acid acylated hormone, highly expressed in the stomach, which binds to its cognate receptor (GHSR1a) to regulate a plethora of relevant biological processes, including food intake, energy balance, hormonal secretions, learning, inflammation, etc. However, ghrelin is, in fact, the most notorious component of a complex, intricate regulatory system comprised of a growing number of alternative peptides (e.g. obestatin, unacylated ghrelin, and In1-ghrelin, etc.), known (GHSRs) and, necessarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 247 publications
(336 reference statements)
4
91
0
Order By: Relevance
“…14 We observed alterations in GOAT mRNA in the brain and the gut of zebrafish under various feeding conditions. Our results indicate that the expression of GOAT mRNA in both brain and gut are influenced by daily feeding period and nutrient status.…”
Section: Figmentioning
confidence: 84%
See 2 more Smart Citations
“…14 We observed alterations in GOAT mRNA in the brain and the gut of zebrafish under various feeding conditions. Our results indicate that the expression of GOAT mRNA in both brain and gut are influenced by daily feeding period and nutrient status.…”
Section: Figmentioning
confidence: 84%
“…44 Several studies in mammals also confirmed that acylated ghrelin and/or GOAT mRNA increases following fasting. 14,40,45 In contrast, other studies either failed to detect an increase in ghrelin or GOAT following fasting, or observed a decrease. 39,46 These discrepancies among studies might be related to the time of food withdrawal, strain of animal used, time of sample collection, type of rodent chow provided, and/ or the method of euthanasia.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the intestine, the large list of hormones include gastrin, cholecystokinin, oxyntomodulin, glucagon-like peptide one and peptide YY [2], all of which act as anorectic agents. In the stomach, among other hormones, there is also ghrelin [3][4][5][6], the only one peptidic hormone that stimulates food intake and adiposity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin was identified in 1999 by screening the endogenous agonist of the growth hormone secretagogue receptor GSHR1a (Howard et al 1996;Kojima et al 1999). Ghrelin is known to be involved in multiple biological functions, such as stimulation of growth hormone secretion, increase of appetite and food intake, and regulation of glucose homeostasis and cardiovascular functions, mediated via the known G protein-coupled receptor GSHR1a or other as yet unknown receptors (Delporte 2013;Gahete et al 2013;Heppner and Tong 2014;Labarthe et al 2014;Pradhan et al 2013;RakMardyla 2013). To prepare a novel bioluminescent ghrelin tracer for non-radioactive receptor-binding assays, a chemically synthesized ghrelin analog (ghrelin-Cys) with a unique cysteine residue at the C-terminus was site-specifically conjugated with an engineered NanoLuc (Luc-Cys) carrying a unique exposed cysteine residue at the C-terminus via a reversible disulfide linkage.…”
Section: Introductionmentioning
confidence: 99%